IMPROVEMENT STUDY RESULT OF SCIENCE THROUGH VISUAL AUDIO MEDIA IN SDN GUNUNG BUNDER 01 PAMIJAHAN BOGOR - Ria Rizki Agustini (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2024)
Most of the sixthgrade students at SDN Gunung Bunder 01 Pamijahan Bogor experience difficulties in learning Natural Sciences (IPA), especially in material for adapting living things to their environment. It was found that out of 18 students, only 8 students (44%) achieved KKM scores and those below KKM there were 10 students (66%). Where the KKM value determined by the school is 70. From the fact above, it is necessary to make efforts to further improve student learning outcomes in the material for adapting living things to their environment. One effort is to use audio-visual media in learning science. Research conducted using the Classroom Action Research approach Suharsimi Arikunto (2017: 19) defines Classroom Action Research as